Investigating Pre-Service Efl Teachers’ Self-Efficacy Beliefs - Eda Ercan Demirel (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The present study aims to shed light on the self-efficacy beliefs of pre-service teachers - who are yet studying at ELT departments. The study searches for the answer of the following research question: “What are the self-efficacy beliefs of pre-service EFL teachers in terms of their forthcoming careers? With a quantitative research design, the study was conducted on pre-service English language teachers yet studying at ELT departments to have their BA degrees at Necmettin Erbakan University, and Gazi University. The participants were senior students 4th grade of ELT department in 2012-2013 Academic Year. 138 Senior students 4th grade of NEU ELT department and 70 Senior students 4th grade of Gazi University ELT department -randomly selected 208 pre-service teachers in total- participated in the study. Out of 208 pre-service teachers, 164 were female, and the rest44- were male. The ages of the participants were between 21 and 25+. The data were gathered through “Teacher Sense of Efficacy scale” originally developed by Tschannen-Moran, Hoy 2001 , the Turkish version of which is developed by Çapa, Çakıroğlu Sarıkaya 2005 . The 24-item-scale was used to collect quantitative data about pre-service teachers’ self-efficacy beliefs. The scale was found to be valid TLI and CFI of .99/RMSEA,.065 and reliable .93 . The scale consists of 3 dimensions of efficacy: Student Engagement, Instructional Strategies, and Classroom Management. Based on the self-efficacy scale, quantitative data analysis was done through SPSS Statistical Package for Social Sciences , version 16.00 and Excel Microsoft Office Professional Plus 2010 . The data analysis revealed that pre-service teachers were sufficient in terms of their self-efficacy and readiness for their future careers. The study also searched for meaningful differences in terms of gender and age variables. It was concluded that there was significant difference between female and male pre-service teachers in favour of females only in Efficacy in Student Engagement dimension . As for the age variable, no significant difference was found.